Akhlaq Education In Elderly Age Islamic Boarding Schools In Indonesia - Mustaqim, Mustaqim -; Sukiman, Sukiman; Sibawaih, Sibawaih (LPPI, 2023)
This research aims to determine the implementation system and process moral education that can lead to successful achievement of goals boarding school for the elderly which includes (1) planning, (2) organizing, (3) implementation, (4) assessment, and (5) supervision of the moral education process at the Izzatul Islam Islamic boarding school in Magelang City. This research uses qualitative methods with the researcher also functioning as the main instrument (key instrument) who goes into the field and tries to collect data himself through observation, interviews and documentation techniques. The results of this research show that; (1) All planning processes for elderly Islamic boarding school moral education from; Determining the material must be a priority scale that suits their learning needs, the material is designed and delivered in such a way as to directly involve the students optimally, planning a learning atmosphere that is conducive to being happy, comfortable, safe and calm for learning. All these aspects have been pursued in accordance with the concept of humanistic management. (2) The organization of the institution, which includes organizers, programs, students, supervisors, curriculum, study schedule and funding, has been attempted and arranged according to a clear schedule and division of tasks. (3) The implementation of moral education for elderly students is strived to be in accordance with the learning climate supported by the andragogy method by making dialogue more effective. (4) Assessment activities include; detailed observations of changes in the behavioral attitudes of each student at the beginning and end of learning, interpreting every symptom that appears from each student which is then described as the assessment results. (5) Supervision in the context of program control includes; pay close attention to learning program planning, pay attention to the organization of learning programs through the division of existing tasks and curriculum preparation, program implementation by direct observation or observation of learning activities carried out inside and outside the classroom, carried out continuously. The results of the study on the impact on the morals of elderly students at the Izzatul Islam Islamic boarding school in Magelang City show that they have increased self-confidence, religious and health knowledge is transmitted or conveyed to their families and other people, they have a positive attitude and are generous towards the community according to their abilities. In addition, the results of learning about the morals of elderly students at the Izzatul Islam Islamic boarding school in Magelang City show that they are increasingly developing a disciplined and orderly lifestyle. Discipline becomes a positive character in their daily lives. The process of moral education at the Izzatul Islam Islamic boarding school increases the motivation of elderly students to achieve husnul khatimah in their old age.